The Effect of Human Resource Planning on the Performance of Police Members - Maryadi, Romi; Shalahuddin, Ahmad; Daud, Ilzar; Rosnani, Titik (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine and analyze the effect of human resource planning on the performance of police members with workload as a mediating variable. Data analysis uses literature studies. The success of an organization will never be separated from the role of human resource performance itself with the optimal quality it provides. In addition, quantity also needs to be considered because completing tasks according to the time given certainly indicates that the performance given is optimal. It is necessary to measure the workload as a basis for calculating optimal workforce needs. This aims to determine the workload and the optimal number of employees. It can be concluded that human resource planning is indeed important to do to produce good performance in an organization. In addition, it can foster high professionalism from each employee so that the workload or tasks given to each employee can be completed properly and organizational goals can be achieved. In other words, human resource planning and workload do affect performance.